Book Reviews (Historia, 2021)
1. H . Bley: South-West Africa under German Rule2. V . H . H . Green: The Later Plantagenets 3. A . L . Harrington: The Great Trek and S . B . Spies: The Origins of the Anglo-Boer War4. H . W . J . Picard: Man of Constantia 5. G . F . Bass: Geschiedenis van de scheepvaart6. H . F . Varion: Some African Milestones7. J . du P . Scholtz: Boonzaaier en Pieter Wenning8. C . Pama: Cape Town . Historic Houses9. W . P . Coolhaas: Het Huis "De Dubbele Arend"10. A . M . Meyerman: Adriaen van der Werff11. Van Stamvenvante Bodem deur dr . J . Ploeger